Transforming pattern-oriented models into component-based models for embedded real-time software development - Abang Jawawi, Dayang Norhayati (2005)
MySEC will provide numerous opportunities for academicians and industry delegates to collaborate and learn from each other. The organisers of this tenth conference believe that the theme “Empowering software engineering towards IOT” will bring a great and brilliant ideas for fruitful interactions and discussions among academics, researchers, and practitioners in sharing their expertise related issues in software engineering.